Validation of a commercially available indirect assay for SARS-CoV-2 neutralising antibodies using a pseudotyped virus assay. Issue 5 (May 2021) - Murray, Matthew J.; McIntosh, Megan; Atkinson, Claire; Mahungu, Tabitha; Wright, Edward; Chatterton, Wendy; Gandy, Michael; Reeves, Matthew B.
Highlights: An ELISA based cPass assay provides a measure of Spike RBD binding antibodies. Binding in a cPass ELISA correlates strongly with pseudotyped virus neutralisation. ELISA-based surrogate assays provide rapid data on neutralising capacity. Abstract: Objectives: To assess whether a commercially available CE-IVD, ELISA-based surrogate neutralisation assay (cPass, Genscript) provides a genuine measure of SARS-CoV-2 neutralisation by human sera, and further to establish whether measuring responses against the RBD of S was a diagnostically useful proxy for responses against the whole S protein. Methods: Serum samples from 30 patients were assayed for anti-NP responses, for 'neutralisation' by the surrogate neutralisation assay and for neutralisation by SARS-CoV-2 S pseudotyped virus assays utilising two target cell lines. Correlation between assays was measured using linear regression. Results: The responses observed within the surrogate neutralisation assay demonstrated an extremely strong, highly significant positive correlation with those observed in both pseudotyped virus assays. Conclusions: The tested ELISA-based surrogate assay provides an immunologically useful measure of functional immune responses in a much quicker and highly automatable fashion. It also reinforces that detection of anti-RBD neutralising antibodies alone is a powerful measure of the capacity to neutralise viral infection.